ECODRAINAGE SYSTEM EVALUATION AND CONTROL OF FLOODS IN JOMBANG DISTRICT, EAST JAVA - Sri Rahmawati; Anita Rahmawati; Azizah Rachmawati (Universitas Islam Malang, 2020)
Jombang sub-district is the most densely populated sub-district because it is located in the middle of Jombang district and is also the center of government. Because it is a densely populated area, resulting in many changes in land use, green land for absorption has turned into a watertight area. The results of the analysis from this aspect indicate that several channels in Jombang District are not able to accommodate the design flood discharge. The calculation of the height of rain design in this study used the Log Person type III method with a return period of 5 years, which resulted in the design rainfall of 157 mm. The results of the analysis show that there are 8 channels out of 74 that are unable to accommodate the design flood discharge. After planning the infiltration wells, a different number was obtained for each road. For Jalan Sentot Prawirodirjo, there are 8 infiltration wells with a reduction power of 51.62%.